A Clinical Study to management of resorbed ridge with Functional Impression Technique in Mandibular Complete Dentures (Journal of Hama University, 2026)
Introduction: the final impression plays an essential role in the complete denture fabrication process especially in the resorbed mandibular ridges as it considered one of the essintal necessities to ensure the success of the complete dentures.Purpose:  the aim of this study was to compare the retention of  resorbed mandibular complete dentures made by functional impression technique using tissue conditioner and conventional impression technique .Materials and Methods: the sample included 12 edentulous patients,ranging in age between (53-72) years .For each patient , two mandibular complete dentures were made ,one by conventional impression technique and the other its was made by closed mouth functional impression technique using tissue conditioner, then a digital force meter was used to measure retention strength provided by each technique, The data obtained was statistically analyzed using Student’s independent T-test, The level of confidence was set at 95%.Results:  There was statistically significant difference in the average mean values of the retention of mandibular complete dentures with functional impression technique and conventional impression   technique  in in research sample at significance level much smaller than the value 0.05. (P-value=0.000).Conclusion: Within the limits of this study, The results showed that the use of functional impression technique in complete dentures for resorbed mandibular increases the retention of the prosthesis as compared with conventional technique
Keywords: : resorbed mandibular, functional impression technique, tissue conditioner , complete dentures